Tree growth, wood anatomy and carbon and oxygen isotopes responses to drought in Mediterranean riparian forests - Camarero, J. Julio; Colangelo, Michele; Rodríguez-González, Patricia M. (Forest ecology and management, 2023)
[Display omitted] •Mediterranean riparian forests are negatively impacted by drought.•Growth responses to climate and drought of four tree species were investigated.•Growth was reduced by drought and low spring-summer river flow.•Populus nigra and Fraxinus angustifolia were the most responsive species to drought.•Ash earlywood anatomy, and wood C and O isotopes also responded to drought. Mediterranean riparian forests have been altered by past use and are also negatively impacted by climate and hydrological droughts. However, we lack data on their historical changes in extent combined with multi-proxy, long-term assessments of tree growth and leaf gas exchange responses to climate, drought severity and river flow. These evaluations must also consider their current stand structure and the amount of lying deadwood which are proxies of river dynamics and forest maturity. To fill these research gaps, we studied four riparian tree species (Populus alba, Populus nigra, Fraxinus angustifolia and Ulmus minor) inhabiting a Mediterranean riparian forest located in north-eastern Spain. We quantified and analyzed: stand structure; lying deadwood; radial growth; relationships between growth, climate variables, the SPEI drought index and river flow; stable C (δ13C) and O (δ18O) isotopes in wood of P. alba, P. nigra and F. angustifolia; and earlywood anatomy in F. angustifolia. Mature sites were dominated by P. nigra and F. angustifolia and showed the highest amount of decayed lying deadwood. Radial growth was reduced by drought and low spring-summer river flow. We found the highest growth responses to 3- (P. nigra, r = 0.62; P. alba, r = 0.46) or 12-month SPEI (F. angustifolia, r = 0.54; U. minor, r = 0.53). The coordinated decrease in δ18O and intrinsic water-use efficiency (WUE) in P. alba and P. nigra could involve an increase in stomatal conductance rate. P. alba and P. nigra were more enriched in δ18O than F. angustifolia, suggesting the former used more enriched shallow groundwater in dry periods. The F. angustifolia WUE and P. nigra δ18O series were positively and negatively correlated with the SPEI, respectively. The F. angustifolia hydraulic diameter decreased in response to drought, whereas its vessel density and WUE were positively associated. Overall, P. nigra and F. angustifolia were the species most responsive to drought.